Submental intubation as an alternative to tracheostomy for patients with panfacial fractures: a case series - Rohra, Divya J.; Patil, Shruti S. (International Journal of Research in Medical Sciences, 2024)
Maxillofacial surgical procedures for panfacial trauma present unique challenges for both surgeons and anesthesiologists. In cases of such injuries, the choice of intubation method becomes critical, especially when temporary airway management is needed intraoperatively due to difficult oral and nasal access and frequent dental occlusion. This study highlighted our experience with submental intubation as an alternative to tracheostomy for airway management in three adult male patients with complex panfacial fractures. The technique of submental intubation involves redirecting the proximal end of an endotracheal tube through the floor of the mouth and the submental region. This approach offers a nontraditional means of airway maintenance with minimal complications and increased safety margins. This study aimed to evaluate the efficacy of submental intubation in managing the airway of patients with complex maxillofacial fractures, assessing factors such as duration of intubation, the incidence of accidental extubation, postoperative complications, as well as a review of literature available previously highlighting the indications, contraindications, advantages, and disadvantages associated with submental intubation. A study of three cases involving panfacial fractures where submental intubation was performed between December 2023 and January 2024 was done. On completion of the procedure, all three patients were successfully extubated on the table without any major intraoperative or postoperative complications.